An integrated cathode and solid electrolyte via in situ polymerization with significantly reduced interface resistance. Issue 96 (22nd November 2021) - Yuan, Jialiang; Dong, Ran; Li, Yuan; Liu, Yang; Zheng, Zhuo; Liu, Yuxia; Sun, Yan; Zhong, Benhe; Wu, Zhenguo; Guo, Xiaodong
Abstract : UV-Curing-based in situ polymerization was used to infiltrate an electrode with solid electrolyte and reduce the interfacial impedance. Abstract : Reducing the interfacial resistance between solid electrolytes and electrodes is critical for developing high-energy density solid-state batteries. In the present study, a simple strategy of designing an integrated cathode and solid electrolyte (ICSE) to avoid a contact interface is proposed and successfully fulfilled with the help of UV curving. Firstly, a porous polymer film (PVDF-HFP/PVDF) was formed on the surface of the porous LiFePO4 electrode via PVP dissolution. Secondly, curable monomers, including PEGDA/PETMP/TFEMA, were filled into the porous membrane via infiltration and concentration. Lastly, the ICSE was obtained via curing with ultraviolet light. The as-prepared LiFePO4 //ICSE//Li solid battery displays excellent electrochemical performance with a high reversible capacity of 153 mA h g −1 and a capacity of over 140 mA h g −1 was retained after 150 cycles at 0.1C and 25 °C. This ICSE strategy may effectively contribute to the practical application of all-solid-state batteries.